2015
DOI: 10.1016/j.bcp.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor (HNF) 4α transactivation of cytochrome P450 (Cyp) 2d40 promoter is enhanced during pregnancy in mice

Abstract: We have recently reported that transactivation of cytochrome P450 (CYP) 2D6 promoter by hepatocyte nuclear factor (HNF) 4α is enhanced during pregnancy, and this is triggered in part by altered expression of small heterodimer partner (SHP) and Krüppel-like factor 9 (KLF9). The objective of this study is to determine whether this is conserved for mouse endogenous Cyp2d gene(s). Among the eight Cyp2d homologs of mouse we examined, only Cyp2d40 expression was found induced (by 6-fold) at term pregnancy as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previous studies reported the involvement of several endogenous and exogenous compounds in the regulation of CYP2D (Baum & Strobel 1997, Waxman & O'Connor 2006, Waxman & Holloway 2009. Although CYP2D isozymes have long been considered as non-hormone inducible drug-metabolizing enzymes (Yu et al 2004, Zanger et al 2004, Ingelman-Sundberg et al 2007, recent studies reported possible roles of sex steroid hormones in CYP2D regulation (Wang et al 2014, Ning et al 2015. However, the mechanisms involved in this regulation were not elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported the involvement of several endogenous and exogenous compounds in the regulation of CYP2D (Baum & Strobel 1997, Waxman & O'Connor 2006, Waxman & Holloway 2009. Although CYP2D isozymes have long been considered as non-hormone inducible drug-metabolizing enzymes (Yu et al 2004, Zanger et al 2004, Ingelman-Sundberg et al 2007, recent studies reported possible roles of sex steroid hormones in CYP2D regulation (Wang et al 2014, Ning et al 2015. However, the mechanisms involved in this regulation were not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2D isoforms are expressed in various tissues, such as the liver, intestine, kidney and brain (Siegle et al 2001, Miksys et al 2005 and, in humans, catalyze the hepatic metabolism of about 25% of the prescribed drugs including the vast majority of antidepressants and antipsychotics, several analgesics, antiarrythmics and anticancer drugs (Yu et al 2004, Zanger et al 2004, Ingelman-Sundberg et al 2007. CYP2D is also implicated in the synthesis and metabolism of neurotransmitters (dopamine and serotonin) (Hiroi et al 1998) and neurosteroids in the human and rat brain (Yu et al 2003, Ning et al 2015 and mainly in brain regions where disturbances in these neurotransmitter systems contribute to the pathophysiology of depression and schizophrenia (Haduch & Daniel 2018). It is also noteworthy that CYP2D6 polymorphisms have been implicated in personality traits and neurological or psychiatric disorders; reduced CYP2D6 activity is associated with increased susceptibility to Parkinson's disease (Smith et al 1992, Lu et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are marked pregnancy‐dependent adjustments in maternal hepatic physiology, and the hepatic changes include genes related to cell proliferation, cytokine signalling, liver regeneration and metabolism in rats 62 . Cytochrome P450 (CYP) 2d40 is upregulated during pregnancy through enhanced transactivation by hepatocyte nuclear factor 4α (HNF4α) in mouse liver 63 . HNF4α is implicated in the regulation of the cytokine‐induced inflammatory response in the liver, 64 which indicates that the hepatic immune response is regulated by pregnancy in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression of many of these enzymes is regulated by HNF 4α [13]. Jeong H and his colleagues reported that promoter transactivation of the cytochrome P450s (CYP) such as CYP2D6, CYP2C9 and CYP2E1 by HNF 4α is enhanced during pregnancy [20,21]. Recombinant HepG2 cells modified by the combination of HNF4α and other transcription factors exhibited enhanced ammonia metabolism and CYP enzyme activity compared with control cells [22].…”
Section: Hnf 4α Regulates Hepatic Differentiationmentioning
confidence: 99%